Genome-wide identification of the MAPK gene family in turbot and its involvement in abiotic and biotic stress responses - Zheng, Weiwei; Xu, Xi-wen; E, Zechen; Liu, Yingjie; Chen, Songlin (Frontiers in Marine Science, 2022)
The mitogen-activated protein kinase (MAPK) gene family performs crucial roles in cell division, migration, development, apoptosis, inflammatory response, and abiotic and biotic stress responses. However, very little information is available about the MAPKs in turbot (Scophthalmus maximus). In this study, 15 turbot MAPKs (SmMAPKs) were identified throughout the whole genome, and their basic chemical and physical properties and subcellular localization were illustrated. All SmMAPKs contained the serine/threonine protein kinases, catalytic domain (S_TKc, SMART00220). Phylogenetic analysis revealed that SmMAPKs were classified into three subfamilies, namely, c-Jun NH2-terminal kinase (JNK), extracellular signal-regulated kinase (ERK), and p38. Conserved motif and gene structure analysis revealed high levels of conservation within and between phylogenetic subfamilies. Expression patterns of MAPKs in distinct tissues and under diverse abiotic and biotic stresses were examined using the published available RNA-seq data sets. As a result, SmMAPKs showed obviously tissue-specific expression. Furthermore, 7 and 10 candidate stress-responsive MAPK genes were detected under abiotic and biotic stresses, respectively, among which five common MAPK genes, namely, SmMAPK4 (ERK4), SmMAPK6 (ERK3), SmMAPK11 (p38β), SmMAPK12b (p38γ), and SmMAPK15 (ERK7/8) showed extremely significant responses to both abiotic and biotic stresses, demonstrating their potential functions in comprehensive antistress. These results demonstrate that MAPKs might play vital roles in response to various abiotic and biotic stresses in turbot, which would contribute to making scientific preventive measures to environmental changes in the process of farming and promoting the development of selective breeding for comprehensive stress resistance in turbot.